Diverse targets of the transcription factor STAT3 contribute to T cell pathogenicity and homeostasis. - Durant, L; Watford, W; Ramos, H; Laurence, A; Vahedi, G; Wei, L; Takahashi, H; Sun, H; Kanno, Y; Powrie, F; O'Shea, J (2010)
STAT3, an essential transcription factor with pleiotropic functions, plays critical roles in the pathogenesis of autoimmunity. Despite recent data linking STAT3 with inflammatory bowel disease, exactly how it contributes to chronic intestinal inflammation is not known. Using a T cell transfer model of colitis, we found that STAT3 expression in T cells was essential for the induction of both colitis and systemic inflammation. STAT3 was critical in modulating the balance of T helper 17 (Th17) and regulatory T (Treg) cells, as well as in promoting CD4(+) T cell proliferation. We used chromatin immunoprecipitation and massive parallel sequencing (ChIP-Seq) to define the genome-wide targets of STAT3 in CD4(+) T cells. We found that STAT3 bound to multiple genes involved in Th17 cell differentiation, cell activation, proliferation, and survival, regulating both expression and epigenetic modifications. Thus, STAT3 orchestrates multiple critical aspects of T cell function in inflammation and homeostasis.